Pengaruh Kualitas Laporan Keuangan Terhadap Akuntabilitas Kinerja Pada Kantor Pengadilan Agama Lubuklinggau - Kusnadi Yudha Wiguna; Anggia Syafitri; Ria Meika Putri (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
The aim of this study is to see the effect of financial report quality toward accountability performance in religious court of Lubuk Linggau. Variables of this study are financial report quality and toward accountability performance. Data of this study is qualitative and quantitative data through questionnaire shared to all religious court officers and financial report validated by Audit Board Republic of Indonesia . The result showed that the quality of financial report gave the significant effect on accountability performance in religious court of Lubuk Linggau by  > , (15,517>1,692) , significant value with 0,000 < 0,05 and determinant cooficient is 0,749 or 74,9 percent.